Real-Time, Energy-Efficient Traction Allocation Strategy for the Compound Electric Propulsion System - Li, Kang; Chou, Fang-Chieh; Yen, Jia-Yush (IEEE/ASME transactions on mechatronics, 2017)
This paper presents the development of a novel compound electric propulsion system for the ground vehicle with the emphasis on real-time, energy-efficient traction control strategy. The proposed compound electric propulsion system employs an induction motor (IM) and two permanent-magnet synchronous motors (PMSMs) to provide traction forces for the front and rear wheels, respectively; such design is aimed to improve energy efficiency and vehicle dynamics performance of conventional electric vehicles (EVs) using IM traction systems by exploiting complementary power characteristics of IM and PMSMs and dynamic traction allocation on all wheels. In this study, a practical traction allocation method, which is based on the power fusion and instantaneous power minimization (IPM) concepts, is proposed to dynamically control the torque loads for the IM and PMSMs such that all motors can be operated in respective high-efficiency regions. The optimal operating points (torque, speed) of IM and PMSMs are searched off-line through the IPM process, and the efficiency maps of the IM and PMSMs are combined and transformed into an optimal efficiency map of the compound electric propulsion system. To verify the feasibility and efficacy of the proposed traction allocation strategy, hardware in the loop simulation experiments were conducted with an active motor dynamometer, IM and PMSM, and a vehicle simulator. Experiments using the U.S. EPA Urban Dynamometer Driving Schedule (FTP-72) show that the compound electric propulsion system with the proposed traction allocation algorithm can reduce energy consumption by ~24% as compared with the conventional IM traction system. In addition, the performance of the proposed traction allocation method is compared with alternative methods and analyzed under different control command update rates.